'May' and 'Shall' and 'Must': Power or Duty?. (23rd November 2018) - Samuels, Alec
Abstract: The words 'may' and 'shall' and 'must' appear in many statutes. Not surprisingly, over the years, a myriad of particular instances has appeared in the law reports. From all this body of law can any principles be deduced? Are there any authoritative texts?